PENGARUH PENGAMPUNAN PAJAK DAN SANKSI PAJAK TERHADAP KEPATUHAN WAJIB PAJAK ORANG PRIBADI - Purnama Dewi Putu; Tiffany Tanudijaya (KRISNA: Kumpulan Riset Akuntansi, 2023)
This study aims to determine the effect of tax amnesty and tax sanctions on individual taxpayer compliance. The sample in this study were 100 people. Data analysis techniques using validity test, reliability test, classic assumption test, multiple linear regression analysis, coefficient of determination test, F test and t test. From the results of the study, it was obtained that the results of tax amnesty had a significant positive effect on individual taxpayer compliance, which meant that significantly increased tax amnesty would lead to increased individual taxpayer compliance registered at the West Denpasar KPP. Tax sanctions have a significant positive effect on individual taxpayer compliance, which means that an increase in tax sanctions will lead to an increase in individual taxpayer compliance registered at KPP Denpasar Barat.